SISTEM PENDUKUNG KEPUTUSAN PENETAPAN RANKING CALON PENERIMA BEASISWA BERBASIS ANALYTICAL HIERARCHY PROCESS (AHP) - Huzainsyahnoor Aksad (STMIK Banjarbaru, 2010)
Determining rank awardees in STMIK Banjarbaru particular and general in Borneo Kopertis Region XI shall be determined based on several criteria, proved by the existence of these criteria could lead to less objective and accurate in stipulating, and could cause delays in the work to determine the ranking of the candidates for scholarship applicants . If potential participants will be increasingly more frequent occurrence of instability objektifan happened, and the longer it is used to determine these rankings.One alternative that could be used is to use Decision Support System for Determination of Rank-Based Prospective Scholars Analytical Hierarchy Process. Analytical Hierarchy Process is a method capable of comparing each criterion with other criteria as well, where the accuracy of this system is much better than using manual systems. The purpose of this research is to implement Analytical Hierarchy Process (AHP) to improve the accuracy in determining ranking in awardees STMIK Banjarbaru.From the analysis result that was seen from the results of Paired Sample t-test of the value before the AHP-based DSS system with after using the system are the result of calculating the value of t> t-table in which 13.822> 2.045 at df 29 and a 5% for two-sided test . From the results it can be implemented that there is a very significant difference between before and after using the Decision Support System for Determining Candidates for AHP-Based Scholarship. Also based on test results of the questionnaire used to assess the existence of the system obtained a valid and reliable results from the four assessments, namely in terms of quality, benefits, data accuracy and data security. Keywords: Decision Support Systems, Analytical Hierarchy Process